PENDAMPINGAN BELAJAR DALAM MENINGKATKAN KREATIVITAS ANAK DI DUSUN BAKALAN BANDONGAN - Sri Hartatik; Cyntia Dwi Saputri (Institut Agama Islam Syubbanul Wathon Magelang, 2024)
Bakalan Hamlet, Bandongan, faces fundamental challenges in children's potential development, namely low creativity and poor learning discipline triggered by the lack of structured parental mentoring and minimal stimulating non-academic activities. Based on the problem analysis (Research) within the Participatory Action Research (PAR) framework, it was found that children tend to spend their leisure time playing gadgets instead of engaging in productive activities. This Community Service (PkM) activity aims to enhance learning discipline and stimulate children's creativity. The Action phase was implemented through face-to-face learning assistance programs combined with creative enhancement sessions, such such as collage making, designing snack bouquets, and free drawing. The results of the Participatory program indicated a significant increase in children's learning discipline and a rise in enthusiasm and the ability to create new works. This PkM program proved effective in shifting children's focus from passive habits to productive activities, providing them with essential knowledge and experience, and holistically improving the quality of learning and creativity in Bakalan Hamlet.